Preparation method of modified nanocellulose aqueous zinc ion battery diaphragm
By forming a coordination structure of copper ions and hydroxyl groups on the nanocellulose membrane and constructing a flexible metal-organic cross-linked network, the problems of insufficient ionic conductivity and mechanical strength of aqueous zinc ion battery membranes were solved, and a high-performance and environmentally friendly battery membrane was achieved.
Patent Information
- Application Number
- CN202510759606.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-09
- Publication Date
- 2025-09-05
AI Technical Summary
Existing aqueous zinc-ion battery separators have deficiencies in ion conductivity, mechanical strength and environmental friendliness, making it difficult to meet the requirements of high safety and low cost.
By forming a coordination structure of copper ions and hydroxyl groups on the surface of nanocellulose, a flexible metal-organic cross-linked network is constructed to regulate the zinc ion deposition behavior, inhibit the growth of zinc dendrites, and maintain the porous structure and hydrophilicity of the membrane.
It significantly improves the mechanical strength and ion transmission performance of the diaphragm, extends the battery cycle life, has good biodegradability, and meets the requirements of green and sustainable development.
Smart Images

Figure CN120601071A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion battery separators, and in particular to a method for preparing a modified nanocellulose aqueous zinc ion battery separator. Background Art
[0002] Traditional lithium batteries have achieved great success in the energy storage market due to their high energy efficiency and high energy density, but their low safety factor, high cost and the use of flammable organic electrolytes have affected their sustainable development. Aqueous zinc-ion batteries are regarded as an ideal choice for the next generation of large-scale energy storage systems due to their high safety, environmental friendliness and low cost. As a key component of the battery, the diaphragm not only needs to prevent direct contact between the positive and negative electrodes, but also needs to have excellent ion conductivity and mechanical strength to inhibit the growth of zinc dendrites and improve battery performance. At present, traditional diaphragms (such as glass fiber diaphragms and polyolefin diaphragms) have problems such as poor mechanical properties, uneven ion flux, and high cost, which make it difficult to meet the needs of aqueous zinc-ion batteries. In order to solve this problem, nanocellulose diaphragm technology is expected to provide a new solution for the development of aqueous zinc-ion batteries and is attracting more and more attention from researchers.
[0003] Nanocellulose, a natural polymer, is considered a sustainable separator material due to its unique properties. Compared to traditional separators, nanocellulose's surface is rich in hydrophilic groups such as hydroxyl groups, which form a good interfacial contact with the electrolyte, thereby improving ionic conductivity. While being thin, it also possesses excellent mechanical properties, effectively inhibiting zinc dendrite growth and enhancing the separator's mechanical strength. Through modification and composite techniques, the anti-swelling properties and electrochemical performance of nanocellulose separators have been significantly improved.
[0004] Application number CN202410404511.3 discloses an aqueous zinc-ion battery separator, its preparation method, and its application, belonging to the technical field of battery separator preparation. The invention provides a preparation method that coats glass fibers with a polyacrylic acid aqueous solution, heat-treats them, and then rinses them with water to form a functional layer on the glass fiber surface. The separator produced by this invention is relatively thick, resulting in a longer ion transmission distance and lower ion conductivity.
[0005] The invention with application number CN202311121480.2 discloses a method for preparing a modified PET-based aqueous zinc-ion battery separator, in which the amino group of the modified PET-based aqueous zinc-ion battery separator can effectively chelate zinc ions, weaken the activity of H2O and Zn2+ in the hydrated zinc ions, and guide the uniform deposition of zinc ions. However, the PET separator itself is hydrophobic and difficult to form a good interface contact with the aqueous electrolyte, resulting in low ion conductivity. In addition, the material of the PET separator is not biodegradable, which will have a long-term impact on the environment and does not meet the requirements of green environmental protection. Summary of the Invention
[0006] The purpose of the present invention is to provide a method for preparing a modified nanocellulose aqueous zinc ion battery separator, aiming to solve the deficiencies of existing aqueous zinc ion battery separators in ion conductivity, mechanical strength and environmental friendliness.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a modified nanocellulose aqueous zinc ion battery separator, comprising the following steps:
[0009] S1. Preparation of nanocellulose (CNF): mixing a cellulose suspension with deionized water, stirring until uniformly dispersed, filtering, and drying to form a nanocellulose film;
[0010] S2. preparing a copper ion crosslinking solution: reacting an alkaline solution with a copper salt solution to generate a clear solution containing copper ions;
[0011] S3, preparing a copper ion modified membrane: mixing the nanocellulose prepared in step S1 with the copper ion-containing clarified liquid prepared in step S2, and washing and drying to obtain a copper ion coordinated nanocellulose membrane (Cu-CNF);
[0012] The copper ions form a coordination structure with the hydroxyl groups of the nanocellulose, thereby enhancing the mechanical strength of the diaphragm, regulating the uniform deposition of zinc ions, and inhibiting the growth of zinc dendrites.
[0013] Preferably, in step S1, the amount of cellulose suspension used is 2g-6g, the amount of deionized water added is 20ml-50ml, the stirring speed is 600rpm-900rpm, the stirring time is 2h-4h, and the drying condition is maintained at 40℃-70℃ for 10h-13h.
[0014] Preferably, in step S1, the amount of cellulose suspension used is 4 g, the amount of deionized water added is 40 ml, the stirring speed is 800 rpm, the stirring time is 3 h, and the drying condition is maintained at 60° C. for 12 h.
[0015] Preferably, step S2 comprises preparing a sodium hydroxide solution and a copper sulfate solution, adding the prepared sodium hydroxide solution dropwise to the copper sulfate solution until a blue precipitate appears, and placing the solution in a centrifuge to separate the supernatant;
[0016] The sodium hydroxide solution preparation process includes: weighing 0.8g-2.0g of sodium hydroxide particles, placing them in a beaker, measuring 10ml-30ml of distilled water, and preparing a 5wt%-9wt% sodium hydroxide solution;
[0017] The copper sulfate solution preparation process includes: weighing 0.4681g-0.6198g of copper sulfate pentahydrate, placing the mixture in a beaker, and measuring 20ml-50ml of distilled water to prepare a 40mmol / L-70mmol / L copper sulfate solution.
[0018] Preferably, the sodium hydroxide solution preparation process includes: weighing 1.6g of sodium hydroxide particles, placing them in a beaker, measuring 20ml of distilled water, and preparing an 8wt% sodium hydroxide solution;
[0019] The copper sulfate solution preparation process includes: weighing 0.5993 g of copper sulfate pentahydrate, placing it in a beaker, measuring 40 ml of distilled water, and preparing a 60 mmol / L copper sulfate solution.
[0020] Preferably, in step S2, the centrifuge speed is 8000 rpm and the centrifugation time is 10 min.
[0021] Preferably, the specific process of the mixing reaction in step S3 includes: weighing 3.1g-3.8g of the nanocellulose suspension, adding the supernatant prepared in step S2 to the cellulose suspension, stirring at room temperature at a speed of 700rpm-900rpm for 11h-13h, filtering and washing with sodium hydroxide, and then placing in a vacuum drying oven at 30℃-50℃ and drying for 4h-6h.
[0022] Preferably, 3.4 g of the nanocellulose suspension is weighed, the supernatant prepared in step S2 is added to the cellulose suspension, stirred at room temperature at 800 rpm for 12 h, filtered, washed with sodium hydroxide, and then placed in a vacuum drying oven at 40° C. for 5 h.
[0023] In a second aspect, an embodiment of the present invention provides an aqueous zinc ion battery separator, which is composed of a copper ion coordinated nanocellulose separator prepared by any of the methods described above, and is used to inhibit zinc dendrite growth and improve battery cycle stability.
[0024] Compared with the existing technology, the beneficial effects of the present invention are: compared with the diaphragms made of traditional polyolefins, glass fibers or modified PET and other materials, the present invention constructs a flexible metal-organic cross-linked network by coordinating copper ions with hydroxyl groups on the surface of nanocellulose, which effectively regulates the deposition behavior of zinc ions and inhibits dendrite growth, while significantly improving the mechanical strength of the diaphragm and reducing the risk of puncture; secondly, copper ions are introduced to regulate the electric field distribution, which is different from the traditional physical doping or polymer coating methods. The selective coordination of metal ions and functional groups is used to form a uniform electric field on the surface of the diaphragm, thereby optimizing the migration path and deposition morphology of zinc ions; by regulating the copper ion complexation mode, the porous structure and hydrophilicity of nanocellulose are maintained, while enhancing the structural stability, avoiding pore blockage and decreased hydrophilicity, and ensuring that the diaphragm has excellent ion transmission performance; natural nanocellulose is used as the base material, which has good biodegradability and environmental adaptability, taking into account both green sustainable development and high-performance energy storage needs. Therefore, the present invention has outstanding innovation and technological advancement in material construction, interface regulation and structural performance coordinated design. It not only significantly improves battery performance and safety, but also conforms to the development trend of future green energy storage, and has broad application prospects and industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The CA curve of the Cu-CNF membrane symmetrical battery in the embodiment of the present invention and the corresponding Nyquist plot before and after the CA test;
[0026] Figure 2 The stress-strain curves of Cu-CNF treated with different NaOH concentrations and CNF treated with NaOH only without copper ion crosslinking in the embodiment of the present invention are shown;
[0027] Figure 3 The stress-strain curves of CNF and Cu-CNF in the embodiment of the present invention;
[0028] Figure 4 This is a cycle diagram of the Cu-CNF membrane symmetrical battery in an embodiment of the present invention at a current density of 1 mA·cm-2 and an area capacity of 1 mAh·cm-2.
[0029] Figure 5 This is the Coulombic efficiency diagram of the Cu-CNF separator Zn||Cu battery. DETAILED DESCRIPTION
[0030] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0031] In a first aspect, the present invention provides a method for preparing a modified nanocellulose aqueous zinc ion battery separator, comprising the following steps:
[0032] S1. Preparation of nanocellulose: mixing a cellulose suspension with deionized water, stirring until uniformly dispersed, filtering and drying to form a nanocellulose film;
[0033] S2. preparing a copper ion crosslinking solution: reacting an alkaline solution with a copper salt solution to generate a clear solution containing copper ions;
[0034] S3, preparing a copper ion modified membrane: mixing the nanocellulose prepared in step S1 with the copper ion-containing clarified liquid prepared in step S2 for reaction, and obtaining a copper ion coordinated nanocellulose membrane after washing and drying;
[0035] The copper ions form a coordination structure with the hydroxyl groups of the nanocellulose, thereby enhancing the mechanical strength of the diaphragm, regulating the uniform deposition of zinc ions, and inhibiting the growth of zinc dendrites.
[0036] This method coordinates copper ions with nanocellulose hydroxyl groups to form a uniform electric field distribution, regulating zinc ion deposition behavior and effectively inhibiting zinc dendrite growth while maintaining high ionic conductivity. This method enhances the mechanical strength of the separator, extends the battery cycle life, and solves the problems of low ion flux and poor mechanical properties of traditional separators.
[0037] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0038] Example 1
[0039] In this embodiment, the amount of cellulose suspension used in step S1 is 2 g, the amount of deionized water added is 20 ml, the stirring speed is 600 rpm, the stirring time is 2 h, and the drying condition is maintained at 40° C. for 10 h.
[0040] In this embodiment, step S2 includes preparing a sodium hydroxide solution and a copper sulfate solution. The prepared sodium hydroxide solution is added dropwise to the copper sulfate solution until a blue precipitate appears, and then placed in a centrifuge to separate the supernatant.
[0041] In this embodiment, the sodium hydroxide solution preparation process includes: weighing 0.8 g of sodium hydroxide particles, placing the particles in a beaker, and measuring 10 ml of distilled water to prepare a 5 wt % sodium hydroxide solution.
[0042] In this example, 0.4681 g of copper sulfate pentahydrate was weighed and placed in a beaker, and 20 ml of distilled water was measured to prepare a 40 mmol / L copper sulfate solution.
[0043] In this embodiment, the centrifuge speed in step S2 is 6000 rpm and the centrifugation time is 8 minutes.
[0044] In this embodiment, the amount of the nanocellulose suspension in step S3 is 3.1 g, and the drying condition is drying in a vacuum drying oven at 30° C. for 4 h. The stirring speed is 700 rpm, and the stirring time is 11 h.
[0045] Example 2
[0046] In this embodiment, the amount of cellulose suspension used in step S1 is 3 g, the amount of deionized water added is 30 ml, the stirring speed is 700 rpm, the stirring time is 3 h, and the drying condition is 50° C. for 11 h.
[0047] In this embodiment, step S2 includes preparing a sodium hydroxide solution and a copper sulfate solution. The prepared sodium hydroxide solution is added dropwise to the copper sulfate solution until a blue precipitate appears, and then placed in a centrifuge to separate the supernatant.
[0048] In this embodiment, the sodium hydroxide solution preparation process includes: weighing 1.0 g of sodium hydroxide particles, placing the particles in a beaker, and measuring 20 ml of distilled water to prepare a 6 wt % sodium hydroxide solution.
[0049] In this example, 0.4890 g of copper sulfate pentahydrate was weighed and placed in a beaker, and 30 ml of distilled water was measured to prepare a 50 mmol / L copper sulfate solution.
[0050] In this embodiment, the centrifuge speed in step S2 is 7000 rpm and the centrifugation time is 9 minutes.
[0051] In this embodiment, the amount of the nanocellulose suspension used in step S3 is 3.4 g, and the drying condition is drying in a vacuum drying oven at 40° C. for 4.5 h. The stirring speed is 800 rpm, and the stirring time is 12 h.
[0052] Example 3
[0053] In this embodiment, the amount of cellulose suspension used in step S1 is 4 g, the amount of deionized water added is 40 ml, the stirring speed is 800 rpm, the stirring time is 3 h, and the drying condition is maintained at 60° C. for 12 h.
[0054] In this embodiment, step S2 includes preparing a sodium hydroxide solution and a copper sulfate solution. The prepared sodium hydroxide solution is added dropwise to the copper sulfate solution until a blue precipitate appears, and then placed in a centrifuge to separate the supernatant.
[0055] In this embodiment, the sodium hydroxide solution preparation process includes: weighing 1.6 g of sodium hydroxide particles, placing them in a beaker, and measuring 20 ml of distilled water to prepare an 8 wt % sodium hydroxide solution.
[0056] In this example, 0.5993 g of copper sulfate pentahydrate was weighed and placed in a beaker, and 40 ml of distilled water was measured to prepare a 60 mmol / L copper sulfate solution.
[0057] In this embodiment, the centrifuge speed in step S2 is 8000 rpm and the centrifugation time is 10 min.
[0058] In this embodiment, the amount of the nanocellulose suspension used in step S3 is 3.4 g, and the drying condition is drying in a vacuum drying oven at 40° C. for 5 h. The stirring speed is 800 rpm, and the stirring time is 12 h.
[0059] Example 4
[0060] In this embodiment, the amount of cellulose suspension used in step S1 is 4 g, the amount of deionized water added is 50 ml, the stirring speed is 900 rpm, the stirring time is 3 h, and the drying condition is maintained at 60° C. for 13 h.
[0061] In this embodiment, step S2 includes preparing a sodium hydroxide solution and a copper sulfate solution. The prepared sodium hydroxide solution is added dropwise to the copper sulfate solution until a blue precipitate appears, and then placed in a centrifuge to separate the supernatant.
[0062] In this embodiment, the sodium hydroxide solution preparation process includes: weighing 2.0 g of sodium hydroxide particles, placing them in a beaker, and measuring 30 ml of distilled water to prepare a 9 wt % sodium hydroxide solution.
[0063] In this example, 0.6198 g of copper sulfate pentahydrate was weighed and placed in a beaker, and 50 ml of distilled water was measured to prepare a 70 mmol / L copper sulfate solution.
[0064] In this embodiment, the centrifuge speed in step S2 is 9000 rpm and the centrifugation time is 11 minutes.
[0065] In this embodiment, the amount of the nanocellulose suspension used in step S3 is 3.8 g, and the drying condition is drying in a vacuum drying oven at 50° C. for 6 h. The stirring speed is 800 rpm, and the stirring time is 12 h.
[0066] Please see the attached Figure 1 , showing the chronopotentiometry (CA) curve and the corresponding electrochemical impedance spectroscopy (EIS) Nyquist plot of the Cu-CNF membrane symmetric battery. It can be seen that in Example 1, the lower cellulose dosage and cross-linker concentration lead to insufficient copper ion coordination, the mechanical strength of the membrane is slightly weak, the uniformity of zinc ion deposition needs to be improved, and the performance is better than the traditional membrane. In Example 2, by appropriately increasing the cellulose dosage and cross-linker concentration, the degree of coordination between copper ions and nanocellulose hydroxyls is improved, and the mechanical strength and ion transfer efficiency of the membrane are significantly improved. In Example 3, by optimizing the cellulose dosage, cross-linker concentration and centrifugal conditions, the coordination structure of copper ions and nanocellulose reaches the best balance, the porosity of the membrane remains stable, the uniformity of zinc ion deposition is significantly improved, the mechanical strength is enhanced, and the comprehensive performance reaches a peak. The voltage of the CA curve remains stable during the test time (such as 700 hours), indicating that the zinc ion deposition is uniform and there is no obvious local polarization caused by dendrite growth. The Nyquist plot shows that the impedance value in the low-frequency region is significantly lower than that of the unmodified CNF membrane, indicating that the ion transfer resistance of the Cu-CNF membrane is reduced. (where R b is the bulk resistance, R ion is the interface resistance), combined with the Figure 1 The EIS data were calculated and it was found that when The zinc ion transfer efficiency is highest when the copper ion is 0.05 wt %. It is verified that the method provided in the embodiment of the present application can obtain a nanocellulose (Cu-CNF) aqueous zinc ion battery diaphragm with copper ion coordination for use in aqueous zinc ion batteries. The method of coordinating copper ions with nanocellulose hydroxyl groups can not only form a uniform electric field distribution on the diaphragm surface and regulate the uniform deposition behavior of zinc ions, thereby effectively inhibiting the growth of zinc dendrites, but also will not significantly block the porous structure of nanocellulose, thereby maintaining efficient ion transmission.
[0067] Please see the attached Figure 2 and attached Figure 3 Symmetrical battery tests showed that the Cu-CNF membrane had no short-circuit phenomenon within 700 hours, while the unmodified CNF had voltage fluctuations after 300 hours. The embodiments of the present application also have nanocellulose coordinated with copper ions, which does not reduce the excellent toughness of the nanocellulose membrane itself, and enhances the mechanical strength of the nanocellulose membrane, effectively preventing dendrite growth from piercing the membrane during charging and discharging.
[0068] Please see the attached Figure 4 and attached Figure 5 In the Zn||Cu half-cell test, the coulombic efficiency of the Cu-CNF membrane is stable at 98.54±0.3%, which is much higher than that of the PET-based membrane (92.1%). Therefore, the method provided in the embodiment of the present application can effectively improve the battery cycle stability and extend the battery cycle life. -2, it can stably cycle for 700 hours with an average coulombic efficiency of 98.54%.
[0069] Based on Example 3, Example 4 further increased the concentrations of NaOH and copper sulfate. The copper ion coordination approached saturation, and the porosity remained unchanged. However, the zinc ion transfer number and cycle efficiency remained essentially the same as in Example 3, indicating that the membrane performance remained stable within a ±10% parameter fluctuation range. Example 3 remains the optimal choice due to its lower raw material consumption and process complexity.
[0070] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a modified nanocellulose aqueous zinc ion battery separator, characterized in that: The steps include: S1. Preparation of nanocellulose: mixing a cellulose suspension with deionized water, stirring until uniformly dispersed, filtering and drying to form a nanocellulose film; S2. preparing a copper ion crosslinking solution: reacting an alkaline solution with a copper salt solution to generate a clear solution containing copper ions; S3, preparing a copper ion modified membrane: mixing the nanocellulose prepared in step S1 with the copper ion-containing clarified liquid prepared in step S2 for reaction, and obtaining a copper ion coordinated nanocellulose membrane after washing and drying; The copper ions form a coordination structure with the hydroxyl groups of the nanocellulose, thereby enhancing the mechanical strength of the diaphragm, regulating the uniform deposition of zinc ions, and inhibiting the growth of zinc dendrites.
2. The method for preparing a modified nanocellulose aqueous zinc ion battery separator according to claim 1, wherein: In step S1, the amount of cellulose suspension used is 2g-6g, the amount of deionized water added is 20ml-50ml, the stirring speed is 600rpm-900rpm, the stirring time is 2h-4h, and the drying condition is 40°C-70°C for 10h-13h.
3. The method for preparing a modified nanocellulose aqueous zinc ion battery separator according to claim 2, wherein: In step S1, the amount of cellulose suspension used is 4 g, the amount of deionized water added is 40 ml, the stirring speed is 800 rpm, the stirring time is 3 h, and the drying condition is maintained at 60° C. for 12 h.
4. The method for preparing a modified nanocellulose aqueous zinc ion battery separator according to claim 3, wherein: Step S2 comprises preparing a sodium hydroxide solution and a copper sulfate solution, wherein the prepared sodium hydroxide solution is added dropwise to the copper sulfate solution until a blue precipitate appears, and the solution is placed in a centrifuge to separate the supernatant; The sodium hydroxide solution preparation process includes: weighing 0.8g-2.0g of sodium hydroxide particles, placing them in a beaker, measuring 10ml-30ml of distilled water, and preparing a 5wt%-9wt% sodium hydroxide solution; The copper sulfate solution preparation process includes: weighing 0.4681g-0.6198g of copper sulfate pentahydrate, placing the mixture in a beaker, and measuring 20ml-50ml of distilled water to prepare a 40mmol / L-70mmol / L copper sulfate solution.
5. The method for preparing a modified nanocellulose aqueous zinc ion battery separator according to claim 4, characterized in that: The sodium hydroxide solution preparation process includes: weighing 1.6g of sodium hydroxide particles, placing them in a beaker, measuring 20ml of distilled water, and preparing an 8wt% sodium hydroxide solution; The copper sulfate solution preparation process includes: weighing 0.5993 g of copper sulfate pentahydrate, placing it in a beaker, measuring 40 ml of distilled water, and preparing a 60 mmol / L copper sulfate solution.
6. The method for preparing a modified nanocellulose aqueous zinc ion battery separator according to claim 5, characterized in that: In step S2, the centrifuge speed is 6000 rpm-9000 rpm, and the centrifugation time is 8 min-11 min.
7. The method for preparing a modified nanocellulose aqueous zinc ion battery separator according to claim 6, characterized in that: The specific process of the mixing reaction in step S3 includes: weighing 3.1g-3.8g of the nanocellulose suspension, adding the supernatant prepared in step S2 to the cellulose suspension, stirring at room temperature at a speed of 700rpm-900rpm for 11h-13h, filtering and washing with sodium hydroxide, and then placing it in a vacuum drying oven at 30°C-50°C and drying it for 4h-6h.
8. The method for preparing a modified nanocellulose aqueous zinc ion battery separator according to claim 7, wherein: 3.4 g of the nanocellulose suspension was weighed, and the supernatant prepared in step S2 was added to the cellulose suspension, stirred at room temperature at 800 rpm for 12 h, filtered, washed with sodium hydroxide, and then placed in a vacuum drying oven at 40° C. for 5 h.
9. An aqueous zinc ion battery separator, characterized in that The invention is composed of a copper ion coordinated nanocellulose membrane prepared by the method according to any one of claims 1 to 8, and is used to inhibit zinc dendrite growth and improve battery cycle stability.
Citation Information
Patent Citations
Preparation method of modified PET-based aqueous zinc ion battery diaphragm
CN117039332A
Aqueous zinc ion battery diaphragm as well as preparation method and application thereof
CN118281481A